SCIENCE TEACHER'S BOOK: ANALYZING ELEMENTARY SCHOOL STUDENTS' CHARACTER VALUES - Asrial, Asrial; Syahrial, Syahrial; Sabil, Husni; Ryan, Josephine; Cox, Robyn; Emmitt, Marie; Rahmi, Rahmi (LPPM Universitas Jambi, 2024)
This study ventures into uncharted territory by delving into the intricate tapestry of character values embodied by elementary school students, as delineated within the pages of the Independent Curriculum Class IV Science Teacher's Book. While the significance of character education in shaping young minds is widely acknowledged, this research pioneers a novel approach by scrutinizing the nuanced portrayal of character values embedded within the curriculum materials tailored for fourth-grade students. Leveraging a qualitative methodology, researchers conducted an exhaustive document study, meticulously collecting and analyzing the requisite literature, including softbooks and hardbooks. The findings unearth a compelling revelation: amidst the prescribed curriculum, certain character values crucial for holistic development are conspicuously absent, potentially undermining the efficacy of the teaching and learning process. Such gaps in character education not only impede academic progress but also exert deleterious effects on students' social and emotional well-being, both within the classroom environment and beyond. By spotlighting these lacunae, this study underscores the imperative for a comprehensive overhaul of character education initiatives, advocating for a more robust integration of essential values into the educational fabric. The research serves as a clarion call for educators and policymakers alike to redouble their efforts in nurturing a generation imbued with exemplary character values, thereby fostering a more compassionate and resilient society.